Gledališki lektor - njegova funkcija in namen v sodobnosti - Vrtačnik, Martin (Jezik in slovstvo, 2012)
The emergence of the role of theatre language consultant ("lektor") in the early 20th century in the Slovene drama theatre is linked to the establishment of a special awareness with regard to the Slovene language on stage and to Slovene public speech in general. In the hundred years since then, the role of theatre "lektor" has changed from that of a guardian of the pronunciation norms of an endangered language to that of a stage speech style editor. This was, among other things, the result of the specific socio-historical conditions of the 20th century and of the development of (Slovene) linguistics. Therefore, the role of the modern theatre "lektor" is (once more) reconsidered in the present article, which opens with an elaboration of the nuances implied in the word "lektor" (in relation to the actual tasks ascribed to the theatre language consultant), then goes on to analyse certain theatre reviews and, finally, presents (professional) contributions of "lektors", who indicate firsthand the modern trends in the shaping of stage speech. On the basis of the topics presented, the conclusion proposes a neologism to name one set of the function, or tasks, performed by the theatre language consultant or "lektor", i.e., "the designer of speech".
Keywords: Slovene; slovenščina; odrski govor; gledališki lektor; oblikovalec govora; dramsko gledališče; gledališka terminologija